RELASI KUASA DALAM KEMASAN PRODUK MAKANAN BERBAHASA ARAB DI INDONESIA - Musoffa Basyir; Ahmad Jaeni; A.Ubaedi Fathuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
Packaged products including Arabic food circulating in Indonesia are made in three main contexts: first, the emergence of neo-liberal strategy in the free market area (at the economic level), and the rise of fundamentalist Islamic movements at the religious level of religion; second, the implementation of halal certification on any food product by MUI; third, Arabic has a strategic position in the Indonesian Muslim community. This study contains semiotic study of communication to other forms of text and discourse and symbols of language on the packaged food products including Arabic language circulating in Indonesia. This study does not only uncover denotative and connotative meanings as a sign, but also the ideologies behind it. This study is important to do because language, including advertising and packaged product, loaded with power because in itself, it appeares as a representative of and space for performances (deployment) a wide range of power. This study managed to lift the veils (social, cultural, political, economic, religious, and others), even in its most subtle and unconscious because it is natural and reasonable.